Addressing surgical inequity for Aboriginal and Torres Strait Islander people in Australia's universal health care system: a call to action. Issue 3 (28th January 2021) - O'Brien, Penny; Bunzli, Samantha; Lin, Ivan; Bessarab, Dawn; Coffin, Juli; Dowsey, Michelle M.; Choong, Peter F. M.
Abstract: Aboriginal and Torres Strait Islander people continue to experience health inequity within the Australian health care system. Little research has examined how disparities in surgical care access and outcomes contribute to Aboriginal health. In this narrative review and call to action, we discuss five care points along the journey to high‐quality surgical care: health care seeking, primary health care services, specialist services, surgery and surgical outcomes. We highlight barriers and disparities that exist along this journey, drawing examples from the field of joint replacement surgery. Finally, we present opportunities for change at the health system, health service and clinician level, calling upon researchers, clinicians and policy makers to confront the surgical disparities experienced by Aboriginal and Torres Strait Islander people. Abstract : Little research has examined how disparities in surgical care access and outcomes contribute to Aboriginal health. In this narrative review and call to action, we discuss five care points along the journey to high‐quality surgical care; health care seeking, primary health care services, specialist services, surgery and surgical outcomes. We highlight barriers and disparities that exist along this journey, drawing examples from the field of joint replacement surgery. Finally, we present opportunities for change at the health system, health service and clinician level, calling upon researchers, clinicians and policy makers to confront the surgical disparities experienced by Aboriginal and Torres Strait Islander people.